2022
DOI: 10.1002/ece3.9124
|View full text |Cite|
|
Sign up to set email alerts
|

Caenorhabditisnematodes colonize ephemeral resource patches in neotropical forests

Abstract: Factors shaping the distribution and abundance of species include life‐history traits, population structure, and stochastic colonization–extinction dynamics. Field studies of model species groups help reveal the roles of these factors. Species of Caenorhabditis nematodes are highly divergent at the sequence level but exhibit highly conserved morphology, and many of these species live in sympatry on microbe‐rich patches of rotten material. Here, we use field experiments and large‐scale op… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 78 publications
1
10
0
Order By: Relevance
“…Additionally, hermaphroditic species tend to have less complex and less sex-biased transcriptomes than gonochoristic species (when considering adults) (Thomas et al 2012), and a transgenic reporter construct survey with eight genes and four Caenorhabditis species revealed widespread spatial variation in gene expression (Barrière and Ruvinsky 2014). Notably, over half of the genes examined C. inopinata and C. elegans (Sloat et al 2022), this lends support to the view that developmental system drift in transcriptomes is common in this group. Regardless, future studies that capture a larger phylogenetic sample as well as a range of postembryonic stages will be required to disentangle these possibilities.…”
Section: Widespread Transcriptional Divergence Across Postembryonic D...mentioning
confidence: 58%
See 1 more Smart Citation
“…Additionally, hermaphroditic species tend to have less complex and less sex-biased transcriptomes than gonochoristic species (when considering adults) (Thomas et al 2012), and a transgenic reporter construct survey with eight genes and four Caenorhabditis species revealed widespread spatial variation in gene expression (Barrière and Ruvinsky 2014). Notably, over half of the genes examined C. inopinata and C. elegans (Sloat et al 2022), this lends support to the view that developmental system drift in transcriptomes is common in this group. Regardless, future studies that capture a larger phylogenetic sample as well as a range of postembryonic stages will be required to disentangle these possibilities.…”
Section: Widespread Transcriptional Divergence Across Postembryonic D...mentioning
confidence: 58%
“…2021). As these species are far more closely related to each other than C. inopinata and C. elegans (Sloat et al . 2022), this lends support to the view that developmental system drift in transcriptomes is common in this group.…”
Section: Discussionmentioning
confidence: 99%
“…We chose to measure fitness through population expansion because of the ecology of C. elegans . In the wild, one to a few nematodes colonize a transient microbial resource, reproduce rapidly, predominantly via self‐fertilization, then disperse to a new patch (Félix & Braendle, 2010 ; Richaud et al, 2018 ; Sloat et al, 2022 ). These microbial resources are highly ephemeral, so demes that reach large population sizes quickly are expected to produce more migrants to colonize new patches.…”
Section: Discussionmentioning
confidence: 99%
“…This result contrasts with prior studies that found a cost of resistance only in food-limited contexts (Boots, 2011;Kraaijeveld & Godfray, 1997) We chose to measure fitness through population expansion because of the ecology of C. elegans. In the wild, one to a few nematodes colonize a transient microbial resource, reproduce rapidly, predominantly via self-fertilization, then disperse to a new patch (Félix & Braendle, 2010;Richaud et al, 2018;Sloat et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In the recent article by Sloat et al ( 2022 ), the following sentence was missed in the Acknowledgments section.…”
mentioning
confidence: 99%